Process and feasibility of implementing guideline recommendations for the care of osteoarthritis in West Africa - Christian Mallen; Simon White; Opeyemi O Babatunde; Krysia Dziedzic; Oladapo Adetunji; Ibidunni Alonge; Tolulope Owoyemi; Ebunoluwa Ayinmode; Adebimpe Ogunbanjo; Adewale Adebajo Adebajo (BMJ Global Health)
Objectives To assess the feasibility of a guideline-informed model of care for osteoarthritis in primary healthcare and community pharmacy settings in the West African context.Methods The 4-phase mixed-methods programme of research undertaken in Southwest Nigeria, West Africa. Phases 1–2 involved contextual adaptation of guideline-informed care—Joint Implementation of Guidelines for OSteoArthritis in West-Africa (JIGSAW-A): (1) focus groups (n=4) with patients, community pharmacists and healthcare professionals (HCPs) to identify patient preferences and support needs of HCPs; (2) stakeholders resource contextualisation/codesign (ie, osteoarthritis guidebook in local languages, HCPs training/support package). Iterative codesign workshops (n=3) using participatory approaches, model osteoarthritis consultation simulations and consensus agreement.Phase 3: following training and a 12-week pilot implementation period, patient-reported quality of care was assessed by the OsteoArthritis Quality Indicator questionnaire (modified 9-item scale 0%–100%, 100%=best), and implementation of the JIGSAW-A model of care was evaluated using the Reach-Effectiveness-Adoption-Implementation-Maintenance framework. Patient and HCP interviews explored barriers and facilitators, usefulness and acceptability. In phase 4, recommendations for further scale-up and wider implementation of integrated osteoarthritis care were specified.Results Phases 1–2 highlight the burden and impact of everyday living with joint pain and misinformation which affects help-seeking. Participants expressed the need for a broad information and education campaign and access to self-management support, which informed iterative contextualisation of osteoarthritis care and patient information resources used to support pilot implementation in phase 3.Over 12 weeks, 12 HCPs (community pharmacies, physiotherapists and doctors) were involved in evaluation across nine sites. Of 369 patient consultations that were reported, high rates of quality indicator achievement were found for self-management advice (97%), topical analgesic use (89%) and exercise recommendations (87%). Compliance with full patient assessment in line with the protocol was poor (17%).Conclusions We found that evidence-based care for osteoarthritis, involving community pharmacies (as a usual first point of call) and other primary care clinicians, is feasible and may improve aspects of care in low-resource settings. Further research is needed to ascertain long-term sustainability and cost-effectiveness.